HER2 Status in Gastric and Gastroesophageal Carcinomas: Evaluation of Histopathological Fingings, Paired ResectionBiopsy Specimens, and the Effect of Neoadjuvant Therapy: A Single Center Study - Yuzuguldu, Resmiye Irmak; Sagol, Ozgul; Unlu, Mehtat; Keskinkilic, Merve; Derici, Serhan; Akpinar, Hale; Sarioglu, Sulen (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Accurately determining the human epidermal growth factor receptor 2 (HER2) status is crucial in identifying suitable candidates for targeted therapy in gastric cancer, considering the cost and potential side effects of anti-HER2 treatments. This study aimed to assess HER2 overexpression/amplification prevalence in gastric and gastroesophageal cancer patients, its correlation with clinicopathological characteristics, and the consistency of HER2 status between biopsy and radical specimens. Materials and Methods: We analyzed data from 667 specimens of 600 gastric/gastroesophageal cancer patients at Dokuz Eylül University Faculty of Medicine from 2012 to 2021. The correlation of HER2 expression and amplification status and clinicopathological parameters were assessed. Furthermore, we compared HER2 status concordance between paired biopsy-radical specimens when both endoscopic and radical materials were present. Additionally, we compared HER2 status before and after treatment in patients receiving neoadjuvant chemotherapy. Results: In our study, +3 HER2 immunohistochemistry results were more common in gastroesophageal junction tumors (23%). Human epidermal growth factor receptor 2 immunohistochemistry positivity and HER2 gene amplification were found to be significantly more common in males, people over 65 years of age, and intestinal morphology. Overall concordance of HER2 status between radical and biopsy materials was 95.5%. Conclusion: The high HER2 concordance between the paired biopsy and radical samples holds significant importance in clinical management. This finding is particularly noteworthy since the HER2 assessment can generally be conducted on small/limited biopsy materials in routine practice. Our study is the most extensive series from Türkiye and the Balkans, which will shed light on our country’s data by investigating the relationship of HER2 with clinicopathological parameters in gastric/gastroesophageal carcinomas. Cite this article as:Yuzuguldu RI, Sagol O, Unlu M, et al. HER2 status in gastric and gastroesophageal carcinomas: evaluation of histopathological findings, paired resection-biopsy specimens, and the effect of neoadjuvant therapy: A single center study. Turk J Gastroenterol. 2025;36(6):357-370.